Modelling of lane departure warning system as car driving assistance using Android based system - Abdullah, Mohamad Syafiq (2017)
The use of driver assistance systems is a current trend in the car industry. However, most driver assistance systems require the use of multiple sensors, increasing the cost of their implementation in cars and making them inaccessible to many users. This project introduced a Lane Departure Warning System which the system monitor and assist driver during driving by using Android mobile device. The assist used rear camera of devices and placed the device at center front of driver dashboard. The rear camera capture the view of driving mode on road and detect the lane via image processing and computer vision techniques. For simulation development of the process is done by using MATLAB Simulink software and Hough Transform algorithm using recorded video and real-time video processing through webcam. Final development of the project was implemented the system to an application of lane departure based on android device. This project enabled to assist driver in real-time monitoring for lane marking on both side of the road lane, if any departing occurring the warning notified via graphical and sound alert.